Bacterial etiologies, antimicrobial susceptibility pattern and associated factors among patients suspected sterile body site infections at Debre Markos Comprehensive Specialized Hospital, Northwest Ethiopia - Admas, Dires; Demeke, Gebreselassie; Adugna, Adane; Esmael, Ahmed (Frontiers in Medicine, 2024)
Background: Sterile body locations are usually associated with clinical urgency and lifethreatening illnesses, and they are typically contaminated with diverse bacterial etiologies. If the bacteria acquire resistance to antimicrobial drugs, the public health crisis will only worsen. In developing countries, drug-resistant bacteria are common because of poor surveillance, diagnostic capacity, and control measures. Early diagnosis, and assessing the drug resistance and factors associated with infection are important to combat the drug resistance and treatment. This study aimed to assess the bacterial etiologies, antimicrobial susceptibility pattern, and possible associated factors among patients suspected of sterile body sites. Methods: A hospital-based cross-sectional study was conducted from June 2022 to August 2022 at Debre Markos Comprehensive Specialized Hospital in Amhara regional state, Ethiopia. One hundred seven study participants were selected using consecutive convenient sampling techniques. A structured questionnaire was used to collect socio-demographic and clinical data. Gram stain was done for a preliminary report and inoculated into blood agar, MacConkey agar, and chocolate agar and incubated aerobically and micro aerobically at 37°C for 24 hours. Antimicrobial susceptibility testing was done by the modified Kirby Bauer's disk diffusion method. Data were analyzed using bivariate and multivariate logistic regression was used. A Pvalue less than 0.05 is considered as statistically significant.The overall magnitude of sterile body site infection among study participants was 7.5% (14/187). The majority of the isolates were Gram-negative bacteria with the predominant species Enterobacter cloacae accounting for 28.57% (4/14). Among isolates 78.57%(11/14) of them were multidrug-resistant isolates. Being inpatient, co-morbidity, and alcohol consumption were significantly associated with sterile body site infection.In our study, Gram-negative bacteria were the predominant bacteria that infects sterile body fluid. The prevalence of multi-drug resistance bacteria isolates was significantly high. Therefore, before prescribing an empirical treatment, a medical professional should identify the bacterial etiology of sterile body fluids and the susceptibility of microbes to the drug.